Is Religion More than a Hobby? Social Media Debates on Germany’s Religious-Political Order during COVID - Lina Rodenhausen (AЯGOS)
This study uses social media comments on news reports about the exemption of religious communities in Germany from COVID-19 restrictions as empirical data for researching a contemporary, everyday understanding of religion as suggested by Michael Bergunder (2014). To analyse the discourse on religion, a qualitative content analysis is applied, which pre-structures the corpus. This allows for diverse attitudes towards policies on religion, as well as their correlations to understandings of religion to be identified. The results show that the contested role of religion in society and its relationship to the state is linked to the struggle over the filling of the concept of religion. Finally, a critical assessment following Bergunder’s approach is applied, emphasizing the need to research the current understanding of religion as a contested concept.